2006
DOI: 10.1258/000456306778904614
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D concentrations in an UK inner-city multicultural outpatient population

Abstract: Background Vitamin D deficiency is still thought to be widespread in the UK and in recent years the number of cases of rickets reported in children has increased. In this study, the distribution of vitamin D and the prevalence of vitamin D deficiency have been determined for a multi-ethnic population from the inner-city area of Birmingham, UK, where a vitamin D testing service has been readily available for over 10 years.Methods Serum 25-hydroxyvitamin D concentration was determined using an automated platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 24 publications
5
50
3
1
Order By: Relevance
“…This is to be expected as the association of low total 25-OH vitamin D concentrations with ethnicity has been reported elsewhere. 11,19,20 There is a statistically significant negative correlation between percentage of non-White population of an LSOA and median total 25-OH vitamin D. There is no statistically significant correlation between IMD and total 25-OH vitamin D, suggesting that the most important variable in determining total 25-OH vitamin D status is ethnicity and not economic status. This conclusion is further strengthened by the data presented in Supplementary Figure 3.…”
Section: Discussionmentioning
confidence: 95%
“…This is to be expected as the association of low total 25-OH vitamin D concentrations with ethnicity has been reported elsewhere. 11,19,20 There is a statistically significant negative correlation between percentage of non-White population of an LSOA and median total 25-OH vitamin D. There is no statistically significant correlation between IMD and total 25-OH vitamin D, suggesting that the most important variable in determining total 25-OH vitamin D status is ethnicity and not economic status. This conclusion is further strengthened by the data presented in Supplementary Figure 3.…”
Section: Discussionmentioning
confidence: 95%
“…The possible reasons for this ethnic difference include variations in skin pigmentation, sun exposure, dietary intake, genetic and cultural factors [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic differences in vitamin D levels have been previously described [6][7][8][9] . In a multiethnic population-based study conducted in the United Kingdom (UK), vitamin D levels are lowest among Asians followed by Afro-Caribbeans and highest among Caucasians 6 . In another UK epidemiologic study, they found an age-adjusted prevalence rate of vitamin D deficiency (<20 μg/L) of 93% among South Asian males 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ford et al [25] have reported widespread vitamin D deficiency in a UK-inner city population, more so in women. The results of the present study support these reports in that females showed a higher prevalence of vitamin D deficiency than males, in the total study population as well as in all age groups.…”
Section: Citationmentioning
confidence: 99%